Straight-tip guidewire versus J-tip guidewire for central venous catheterisation in neonates and small infants: A randomised controlled trial. Issue 8 (7th August 2022) - Kim, Eun-Hee; Kang, Pyoyoon; Song, In Sun; Ji, Sang-Hwan; Jang, Young-Eun; Lee, Ji-Hyun; Kim, Hee-Soo; Kim, Jin-Tae
Abstract : BACKGROUND: Central venous catheterisation in neonates and infants is challenging because of the small size of the vessels. The curve of the J-tip guidewire causes difficulty when inserting because of the larger radius and the tilted angle of the J-tip. OBJECTIVE: We hypothesised that a straight-tip guidewire can facilitate guidewire insertion and improve the first-attempt success rate of central venous catheterisation. DESIGN: A randomised controlled study. SETTING: This study was performed between September 2018 and July 2021 in tertiary care children's hospital. PATIENTS: We enrolled infants weighing less than 5 kg undergoing general anaesthesia. INTERVENTIONS: Patients were randomly allocated to the straight-tip or J-tip groups. Ultrasonography-guided catheterisation was performed using the assigned guidewire. MAIN OUTCOME MEASURES: The primary outcome was the first-attempt success rate of central venous catheterisation. The secondary outcomes included the number of guidewire insertion attempts, the time required for successful guidewire insertion, and total time for central venous catheter placement. RESULTS: Eighty-eight patients were studied. The straight-tip group showed a higher first attempt success rate than the J-tip group (86.3 vs. 61.3%, P  = 0.007, odds ratio 4.0, 95% confidence interval (CI), 1.4 to 11.4]. Guidewire insertion attempts were higher in the J-tip group than in the straight group ( P  = 0.002, odds ratio 9.6, 95% CI, 7.9 to 92.9). Although the guidewire insertion time was longer in the J-tip group ( P  = 0.003, median difference 23.0 s, 95% CI, 7.0 to 48.0), the total catheterisation time was similar owing to the additional guidewire change process in the straight-tip group ( P  = 0.676). CONCLUSION: In neonates or infants weighing less than 5 kg, central venous catheterisation using a flexible straight-tip guidewire can improve the first-attempt success rate compared with a J-tip guidewire. TRIAL REGISTRATION: ClinicalTrials.gov, identifier: NCT03530618.